Abrahamic Reflections on Randomness and Providence - Clark, Kelly James; Koperski, Jeffrey (Springer Nature, 2022)
This open access book addresses the question of how God can providentially govern apparently ungovernable randomness. Medieval theologians confidently held that God is provident, that is, God is the ultimate cause of or is responsible for everything that happens. However, scientific advances since the 19th century pose serious challenges to traditional views of providence. From Darwinian evolution to quantum mechanics, randomness has become an essential part of the scientific worldview. An interdisciplinary team of Muslim, Christian and Jewish scholars-biologists, physicists, philosophers and theologians-addresses questions of randomness and providence.